Development of 21st Century Learning Skills Assessment Instruments in STEM-Based Science Learning (Science, Technology, Engineering, and Mathematics) - Binar Ayu Dewanti; Agus Santoso (IKIP Mataram, 2020)
This study aimed to develop a valid, practical, and effective 21st century learning skills assessment instrument for STEM-based science learning. This representation assessment instrument was developed with a 4 D development model with four stages, namely: definition, design, development, and distribution. The 21st century learning skills that are the focus of assessment in this instrument include critical thinking skills, creativity, communication, and collaboration. The subjects of this study consisted of 2 expert validators, 1 science teacher, and 26 students of grade VII SMP at SMPN 2 Sugio, Lamongan. Data collection methods used in this research is validation, questionnaire, observation, and documentation. Data analysis used in this study is the method of obtaining an average for each indicator, aspect, to the total mean, which is then referred to in the interval determining the level of validity & practicality of the product (scale 1-3), as well as statistical testing of paired sample T-test with descriptive statistical analysis. The results of this study are that the 21st century learning skills assessment instrument in STEM-based science learning is valid with a validity score of 2.87, is very practical to use (with a practicality score of 3), and has a positive effect on student learning skills.